Dyskretny chaos w systemach ekonomicznych - Guzowska, Małgorzata (Discrete Chaos in Economic Systems, 2006)
Considerations presented in paper referring to the dynamic models described by difference equations are focussed on their non-linear form. Discovery of new mathematical laws and increasing numerical capabilities in the last decade caused increase of interest in non-linear dynamic models, which behaviour differs from behaviour of linear models. The non-linear models apart from the dynamic analysis allow observing chaotic behaviours that are generated by them. Also, economists noticed that introduction of non-linearity allows better presentation of issues that cannot be explained by means of the simple models. The goals of the paper were: collecting of economic models described by non-linear difference equations, presentation of methods of analysis of dynamics for nonlinear difference equations, application on above-presented methods in analysis of dynamic properties of discussed models, indication of usefulness of methods of analysis of dynamics for non-linear difference equations at trials of use of methods of control of behaviour of chaotic models. The paper presents cause-effects relationships P-S-R, its particular modifications and sustainable development rules as a pillars of sustainable development indicators system. Another structure of indicators were presented in this study. The example of air quality indicators are included.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 40-48